PENERAPAN PRINSIP ANDRAGOGI DALAM BIMBINGAN DAN KONSELING BELAJAR - Nor Hidayah; Hiryanto Hiryanto (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The application of andragogy principles in learning guidance and counseling is an interesting research subject in order to increase the effectiveness of the learning process for adult counselees. This study aims to explore and analyze the application of Andragogy principles in the context of tutoring and counseling, as well as to identify the benefits resulting from this application. The research method used is a literature review. The results of the study show that the application of andragogy principles in study guidance and counseling provides a number of benefits for adult counselees. This study provides insights for counselors in designing and implementing effective and relevant interventions for adult counselees. By utilizing the principles of andragogy, counselors can create a learning environment that supports, motivates, and empowers adult counselees to achieve their learning goals